Small-angle neutron scattering studies of an adsorbed non-ionic surfactant (C12E24) on hydrophobised silica particles in water - Dale, Phillip J (Langmuir : the ACS journal of surfaces and colloids, 2005)
Small-angle neutron scattering (SANS) studies of aqueous dispersions of Stöber silica particles (which have been hydrophobised by having 1-octadecanol grafted to their surface), carrying an adsorbed layer of the nonionic surfactant C12E24, in water, have been performed as a function of temperature. Using mixtures of D2O and H2O, the composition of the continuous phase was adjusted to have the same scattering length density as the silica particles. Hence, only the scattering from the 1-octadecanol and C12E24 layers was detected. The data have been analyzed using both a surface Guinier analysis and a two-layer structure model. It has been found that a step profile best describes the inner combined adsorbed layer (1-octadecanol grafted chains, plus the penetrating alkyl chains from the surfactant) and a semi-Gaussian profile the extended poly(ethylene oxide) outer layer. Both analyses demonstrated that the combined surface layer contracted with increasing temperature